Epistemological Integration of the Concept of God in Western and Eastern Philosophical Discourse - Arauf, Muta Ali (International Tatho Academics, 2026)
The concept of God is one of the central themes in philosophical studies, both in Western and Eastern traditions. Differences in cultural background, history, and frameworks of thought have given rise to various understandings of God, ranging from theism and deism to pantheism and non-theism. This article aims to examine and integrate the concept of God in Western and Eastern philosophy through a literature review approach. The method used is a literature study of classical and contemporary philosophical works. The results of the study show that despite differences in rational and intuitive approaches, Western and Eastern philosophy have common ground in their efforts to understand the highest reality as the source of existence and meaning of life. This study contributes to the affirmation that the integration of these two traditions opens up space for constructive philosophical dialogue in understanding God holistically.